Understanding Patient Barriers to Kidney Transplant Evaluation - Dageforde, Leigh Anne (Transplantation, 2015)
BACKGROUND: Some patients referred for kidney transplant evaluation fail to attend the visit. Our goal was to compare demographic, socioeconomic, and psychological factors between evaluation visit attendees and absentees. METHODS: A convenience sample of patients referred and scheduled for kidney transplant evaluation at a single center from November 2012 to December 2013 participated in a phone survey reporting socioeconomic, demographic and clinical characteristics; health literacy; and perceived knowledge and concerns about transplantation. Absentees were matched by race with attendees. Analyses of differences between groups were performed with Chi-square, Fisher’s exact test, and t-tests. Multivariable logistic regression adjusted for relevant demographic characteristics. RESULTS: 104 adults participated (61% male, 46% Caucasian, 52±12 years). Financial concerns were the most prevalent (67.3% affording medication, 64.1% affording operation). Prior evaluation at a different transplant center (p=0.029) and being on dialysis (p=0.008) were significantly associated with absence. Attendance was associated with concerns about finding a living donor (p=0.038) and higher perceived general knowledge about transplantation (p ≤0.001). No differences were appreciated in demographic, socioeconomic or health literacy factors between groups. CONCLUSIONS: Both attendee and absentee patients were most concerned with the financial burden of kidney transplantation. While concerns and perceived knowledge are important correlates of behavior, other considerations such as psychological factors and prior medical experiences may influence patients’ ability to complete the kidney transplant evaluation process. Although this pilot study was conducted in a small sample and has limited generalizability, our findings can guide future research.